2011
DOI: 10.6009/jjrt.67.1183
|View full text |Cite
|
Sign up to set email alerts
|

A New Method of Measuring Effective Energy Using Copper-pipe Absorbers in X-ray CT

Abstract: The general method of measuring the half-value layer (HVL) for X-ray computed tomography (CT) using square aluminum-sheet filters is inconvenient in that the X-ray tube has to be set to stationary mode. To avoid this inconvenience, we investigated a new method using copper-pipe filters that cover the ionization chamber (copper-pipe method). Using this method, the HVL can be measured at the isocenter in the rotation modes of CT. We examined the accuracy and reproducibility of the copper-pipe method compared wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Second, although the effective photon energy varies among CT scanners, we did not compare the image quality of scans obtained with instruments from different vendors. Others 16,17 reported that the effective photon energy on Toshiba scanners was very low (35.4e39.1 keV at 80 kVp). Therefore, scanners from vendors other than Toshiba may require a higher CM dose even at identical tube voltage settings, and the dose should be determined by the effective photon energy of the scanner used.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Second, although the effective photon energy varies among CT scanners, we did not compare the image quality of scans obtained with instruments from different vendors. Others 16,17 reported that the effective photon energy on Toshiba scanners was very low (35.4e39.1 keV at 80 kVp). Therefore, scanners from vendors other than Toshiba may require a higher CM dose even at identical tube voltage settings, and the dose should be determined by the effective photon energy of the scanner used.…”
Section: Discussionmentioning
confidence: 98%
“…Cheng et al 15 reported differences in contrast enhancement on different CT scanners. As the 320-row CT scanner we used features lower photon energy and yields strong contrast enhancement, 16,17 we hypothesized that its combination with the low-tubevoltage technique (80 kVp with iterative reconstruction [IR]) would reduce both the radiation and CM dose and yield sufficient image quality of proximal and distal coronary vessels.…”
Section: Introductionmentioning
confidence: 99%
“…2, the effective energy of the scattered X-rays would exceed 45 keV according to the Ref. [25] regarding the X-ray energies of used apparatus. With this highly effective energy, we detected a difference in the X-ray transmission rates above 8 % in an experimental field (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, the measurement of HVL in computed tomography (CT) is complicated because the X‐ray tube has to be accurately placed using the unit’s service engineering mode. For increased test validity, several researchers have investigated different methods to measure HVL while the X‐ray tube is rotating …”
Section: Introductionmentioning
confidence: 99%
“…The copper pipe method, which is one of the HVL evaluation methods, uses general‐purpose ionization chamber and several thicknesses of copper pipes to determine HVL. The copper pipes were fabricated to attach general purpose ionization chamber (6 cc thimble).…”
Section: Introductionmentioning
confidence: 99%